LEARNERS' PERSPECTIVES ON USING THE FORVO WEBSITE AS A STRATEGY TO ENHANCE SPEAKING SKILLS - Zaki, Alwan Ammar; Hermansyah; Jaya, Aswadi (Esteem Journal of English Education Study Programme, 2024)
This qualitative case study investigated learners’ perspectives on using the Forvo website to enhance their English-speaking skills within an online Discord community, "The English Hub." Data were collected through questionnaires, interviews, and textual analysis of Discord conversations. Inductive thematic analysis revealed that students perceived Forvo as a valuable tool, aligning with Previous Research, Vygotsky's Sociocultural Theory and TELL principles. Forvo facilitated social interaction, provided access to native speaker pronunciations (MKOs), and served as a cultural tool, promoting pronunciation improvement, confidence building, and vocabulary acquisition. Students reported significant improvements in their speaking skills, particularly in pronunciation, accent reduction, and fluency. Forvo effectively complemented traditional learning methods, offering authentic pronunciation models, a supportive online community, and a user-friendly interface. This study highlights the potential of Forvo to empower learners in their pursuit of English fluency